2021
DOI: 10.3389/fonc.2021.638223
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Genetically Abnormal Cells Add Non-Invasive Diagnosis Value to Discriminate Lung Cancer in Patients With Pulmonary Nodules ≤10 mm

Abstract: BackgroundLung cancer screening using low-dose computed tomography (LDCT) often leads to unnecessary biopsy because of the low specificity among patients with pulmonary nodules ≤10 mm. Circulating genetically abnormal cells (CACs) can be used to discriminate lung cancer from benign lung disease. To examine the diagnostic value of CACs in detecting lung cancer for patients with malignant pulmonary nodules ≤10 mm.MethodsIn this prospective study, patients with pulmonary nodules ≤10 mm who were detected at four h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Moreover, the diagnostic value of CACs in comparison with other traditional biomarkers has been confirmed using a cohort of patients with lung nodules, which is an independent validation to the work conducted by Ye et al [ 24 ]. In the present study, the highest diagnostic efficiency was achieved when a CAC counts of 3 was chosen as the cut-off value, this result is similar to the study conducted by Qiu [ 25 ] and Ye [ 18 ] et al Overall, CAC counts presented better diagnostic value than commonly used tumour markers (CEA, CYFRA21–1, and NSE), which agrees with the results of several studies reporting the advantages of CACs for the diagnosis of lung cancer [ 17 , 18 , 24 , 25 , 27 ], CACs have the potential to become a better novel diagnostic marker of lung cancer.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, the diagnostic value of CACs in comparison with other traditional biomarkers has been confirmed using a cohort of patients with lung nodules, which is an independent validation to the work conducted by Ye et al [ 24 ]. In the present study, the highest diagnostic efficiency was achieved when a CAC counts of 3 was chosen as the cut-off value, this result is similar to the study conducted by Qiu [ 25 ] and Ye [ 18 ] et al Overall, CAC counts presented better diagnostic value than commonly used tumour markers (CEA, CYFRA21–1, and NSE), which agrees with the results of several studies reporting the advantages of CACs for the diagnosis of lung cancer [ 17 , 18 , 24 , 25 , 27 ], CACs have the potential to become a better novel diagnostic marker of lung cancer.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, the traditional mode of small lung nodule diagnosis should be investigated. Previous works as well as this work suggest that CACs are an ideal candidate marker, as such a test only requires the simple process of blood collection and its accuracy has been reported in early lung cancer patients [ 18 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…With the advantages of an early appearance in the disease course, cancer specificity, biological stability, and ready accessibility in bodily fluids [ 81 ], aberrant DNA methylation analysis combined with machine learning provided the opportunity to overcome the challenge of the low abundance of ctDNA in plasma samples [ 28 , 29 , 34 , 58 , 82 , 83 ]. CTCs in the blood could serve as effective screening and diagnostic markers to discriminate small malignant pulmonary nodules from benign lesions [ 54 , 56 ]. The profiling of circulating microRNAs has promising accuracy for discriminating lung cancer patients from healthy controls and could be developed as a supplement in future screening [ 51 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Common evaluation methods include imaging, gene detection, and tumor-related marker detection. Ye et al ( 3 ) conducted a prospective study of 125 preoperative patients with NSCLC with nodules of 1 cm or less. Their analysis showed that patients with pulmonary nodules of 10 mm or less detected by circulating genetically abnormal cells (CACs) before operation could effectively diagnose lung cancer and help doctors choose the appropriate treatment.…”
mentioning
confidence: 99%